Reactivation of Meristem Activity and Sprout Growth in Potato Tubers Require Both Cytokinin and Gibberellin - Hartmann, Anja; Senning, Melanie; Hedden, Peter; Sonnewald, Uwe; Sonnewald, Sophia (Plant Physiology, 2011)
Reactivation of dormant meristems is of central importance for plant fitness and survival. Due to their large meristem size, potato (Solanum tuberosum) tubers serve as a model system to study the underlying molecular processes. The phytohormones cytokinins (CK) and gibberellins (GA) play important roles in releasing potato tuber dormancy and promoting sprouting, but their mode of action in these processes is still obscure. Here, we established an in vitro assay using excised tuber buds to study the dormancy-releasing capacity of GA and CK and show that application of gibberellic acid (GA(3)) is sufficient to induce sprouting. In contrast, treatment with 6-benzylaminopurine induced bud break but did not support further sprout growth unless GA(3) was administered additionally. Transgenic potato plants expressing Arabidopsis (Arabidopsis thaliana) GA 20-oxidase or GA 2-oxidase to modify endogenous GA levels showed the expected phenotypical changes as well as slight effects on tuber sprouting. The isopentenyltransferase (IPT) from Agrobacterium tumefaciens and the Arabidopsis cytokinin oxidase/dehydrogenase1 (CKX) were exploited to modify the amounts of CK in transgenic potato plants. IPT expression promoted earlier sprouting in vitro. Strikingly, CKX-expressing tubers exhibited a prolonged dormancy period and did not respond to GA(3). This supports an essential role of CK in terminating tuber dormancy and indicates that GA is not sufficient to break dormancy in the absence of CK. GA(3)-treated wild-type and CKX-expressing tuber buds were subjected to a transcriptome analysis that revealed transcriptional changes in several functional groups, including cell wall metabolism, cell cycle, and auxin and ethylene signaling, denoting events associated with the reactivation of dormant meristems.